Roots and Emergence of Trumpet Jazz Music Education - Ruochi, Yan; Pattananon, Nicha; Poonsawat, Nopadon (Journal of Roi Kaensarn Academi, 2024)
The history of jazz trumpet education is deeply intertwined with the evolution of jazz music itself. Jazz trumpet has played a pivotal role in shaping the genre’s expressive and improvisational characteristics. In the early 20th century, pioneers like Louis Armstrong and Bix Beiderbecke laid the foundation for jazz trumpet techniques and styles. As jazz evolved, trumpet players such as Dizzy Gillespie, Miles Davis, and Clifford Brown expanded the possibilities of the instrument through innovative techniques and improvisational approaches. The development of jazz trumpet teaching systems has been influenced by various educational philosophies and pedagogical approaches. In the United States, the jazz education movement gained momentum during the mid-20th century, with institutions like Berklee College of Music and the Juilliard School leading the way. These institutions emphasized a comprehensive curriculum that combined technical proficiency, theoretical knowledge, and improvisational skills. This article presented roots and emergence of trumpet jazz education.